Babe - Miller, George, $d 1945 Mar. 3-; Mitchell, Doug (Universal City Universal Studios, 2006)
Babe: A shy Yorkshire piglet is adopted by an old sheep dog and discovers that he can be anything he wants to be
Babe: full frame presentation (1.33:1). Babe : pig in the city: anamorphic widescreen (1.85:1) or full frame (1.33:1) presentation
Originally released as motion pictures in 1995 and 1998
2
Keywords: Domestic animals -- Drama; Piglets -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs